Analisis Pengaruh Digital Marketing dan Dukungan Pemerintah terhadap Kesuksesan UMKM di Kota Medan - Felicia Felicia; Jevkin Jevkin; Dede Ansyari Guci; Puspa Liza Ghazali (IPM2KPE, 2024)
This research aims to analyze the influence of digital marketing and government support on the success of Micro, Small and Medium Enterprises (MSMEs) in Medan City. The research method used involved a survey of MSME owners as well as quantitative data analysis to measure the level of influence of digital marketing and government support. The research results show that there is a positive relationship between effective digital marketing strategies and the level of success of MSMEs. Apart from that, government support, both in the form of policies and facilities, also has a significant positive impact on the development of MSMEs in Medan City. The conclusions of this research emphasize the importance of integrating effective digital marketing strategies and government support in improving the performance and competitiveness of MSMEs, as well as providing a basis for developing policies that support the growth of the MSME sector at the local level. Keywords: Digital Marketing, Government Support, Success